Between global and local: translation and localization in Netflix Turkey’s media paratexts - (:unkn) unknown (My University, 2023)
This study analyses Netflix Turkey’s media paratexts in which Netflix’s foreign productions and Turkish originals are promoted by the creative use of local elements and/or culture-specific references. It aims to identify the role of translation in these paratexts in promoting both Netflix and its shows such as Stranger Things among others in Turkey. It also discusses the functions of these paratexts in relation to their socio-political contexts of production and the wider debates around regulation and censorship in Turkey. The analysis shows that translation and localization in the selected paratexts serve to make the foreign shows relatable, evoke a sentiment of nostalgia and create a sense of belonging. Further, the paratexts on Netflix Turkish originals highlight the untranslatability and culture-specificity of Turkish expressions to appeal to the viewers’ national pride, which is arguably informed by a populist approach due to the increasing possibility of restrictions on content.
Keywords: Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; DİL VE DİLBİLİM; Arts & Humanities (AHCI); ARTS & HUMANITIES; LANGUAGE & LINGUISTICS; Dil ve Dilbilim; Sosyal Bilimler ve Beşeri Bilimler; Dilbilim ve Dil; Language and Linguistics; Social Sciences & Humanities; Linguistics and Language; localization; media; Netflix Turkey; Paratexts; translation; Paratexts; localization; translation; media; Netflix Turkey